Performance modulations phase-locked to action depend on internal state - Tommaso Tosato; Guillaume Dumas; Gustavo Rohenkohl; Pascal Fries (iScience)
Summary: Previous studies have shown that perceptual performance can be modulated at specific frequencies phase-locked to self-paced motor actions, but findings have been inconsistent. To investigate this effect at the population level, we tested 50 participants who performed a self-paced button press followed by a threshold-level detection task, using both fixed- and random-effects analyses. Contrary to expectations, the aggregated data showed no significant action-related modulation. However, when accounting for internal states, we found that trials during periods of low performance or following a missed detection exhibited significant modulation at approximately 17 Hz. Additionally, participants with no false alarms showed similar modulation. These effects were significant in random effects tests, suggesting that they generalize to the population. Our findings indicate that action-related perceptual modulations are not always detectable but may emerge under specific internal conditions, such as lower attentional engagement or higher decision criteria, particularly in the beta-frequency range.